2016
DOI: 10.4137/cmamd.s40237
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lymph Node Volume and Pain following Certolizumab Therapy for Rheumatoid Arthritis Flare: A Pilot Study

Abstract: OBJECTIVESThe mechanisms that trigger flare in rheumatoid arthritis (RA) are unknown. In murine arthritis models, dysfunctional lymph node (LN) drainage is associated with joint flare. To examine if LN alterations are associated with RA flare, we analyzed the change in LN volume via contrast-enhanced magnetic resonance imaging (CE-MRI) in patients with active joint flare at baseline and 16 weeks after certolizumab pegol (CZP) therapy. We also assessed the changes in popliteal or epitrochlear LN volumes versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Pro-inflammatory cytokines, in addition to their roles in disease progression in inflamed joints, have been implicated in arthritic pain development, but also generally in pain progression [ 1 , 2 ]. For example, inhibition of the action of tumour necrosis factor (TNF) [ 3 , 4 ] or granulocyte macrophage-colony stimulating factor (GM-CSF) [ 5 ] ameliorates joint pain in animal models of inflammatory arthritis and also clinically in RA patients [ 6 , 7 ]. We recently described a new GM-CSF➔CCL17 pathway in monocytes/macrophages in vitro, which we found to be important in vivo not only for inflammatory arthritic pain and disease development [ 8 10 ], but also for osteoarthritic pain and disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-inflammatory cytokines, in addition to their roles in disease progression in inflamed joints, have been implicated in arthritic pain development, but also generally in pain progression [ 1 , 2 ]. For example, inhibition of the action of tumour necrosis factor (TNF) [ 3 , 4 ] or granulocyte macrophage-colony stimulating factor (GM-CSF) [ 5 ] ameliorates joint pain in animal models of inflammatory arthritis and also clinically in RA patients [ 6 , 7 ]. We recently described a new GM-CSF➔CCL17 pathway in monocytes/macrophages in vitro, which we found to be important in vivo not only for inflammatory arthritic pain and disease development [ 8 10 ], but also for osteoarthritic pain and disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…macrophage-colony stimulating factor (GM-CSF) [5] ameliorates joint pain in animal models of inflammatory arthritis and also clinically in RA patients [6,7]. We recently described a new GM-CSF➔CCL17 pathway in monocytes/macrophages in vitro, which we found to be important in vivo not only for inflammatory arthritic pain and disease development [8][9][10], but also for osteoarthritic pain and disease [10].…”
mentioning
confidence: 99%
“…We have focused on the synovial lymphatic system during arthritic progression and flare (10,12,16,20,25,26,35,43,44), and the effects of interventions that specifically target lymphatic contractions, whose physiologic importance in supporting lymphatic drainage and subsequent onset of lymphedema have been established in preclinical and clinical studies (7,29,45,46). We have also performed transmission electron microscopy studies on WT, Expanding and Collapsed PLVs (42).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we used CE-MRI to show that RA patients with the smallest change in lymph node volume during anti-TNF therapy experienced the greatest pain relief in symptomatic knee joints with a remarkably linear inverse correlation (28). Most recently, we utilized NIR-ICG imaging (10) to show that lymphatic drainage in the hands of RA patients with active disease is decreased compared to healthy controls (29).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies of lymphadenopathy in RA patients have shown significant alterations in the size and morphology of draining lymph nodes. In a small cohort of RA patients experiencing flares, contrast-enhanced magnetic resonance imaging of draining lymph nodes displayed a reduction of lymph node volume after treatment (18). Manzo and colleagues used power Doppler ultrasound (PDUS) imaging of the axillary lymph nodes in RA patients with active hand disease to demonstrate hypertrophy of the node cortex without clinical lymphadenopathy, along with a strong PDUS signal in the cortical and hilar regions (19).…”
Section: Introductionmentioning
confidence: 99%